2012
DOI: 10.17159/2078-516x/2012/v24i1a360
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year investigation into the incidence and nature of cricket injuries in elite South African schoolboy cricketers

Abstract: Objectives. Injury surveillance is fundamental to preventing and reducing the risk of injury. The aim of this study is to determine the incidence of the injuries sustained by elite schoolboy cricketers over three seasons (2007 - 2008, 2008 - 2009, 2009 -2010) to identify possible risk factors.Methods. Sixteen provincial age-group cricket teams (Under 15, Under 17 and Under 18) competing in national age-group tournaments were asked to complete questionnaires to obtain the following information for each injury: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Test, one day and T20 match types were clearly defined in only four studies 5 7 23 39 . Three studies reported on test and one day matches only 25 28 46 , while two other studies reported on one day and T20 24 31 . Two separate studies reported injuries in one day cricket only 36 47 .The use of a helmet at the time of sustaining a HNF injury was only reported in three studies 11 29 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Test, one day and T20 match types were clearly defined in only four studies 5 7 23 39 . Three studies reported on test and one day matches only 25 28 46 , while two other studies reported on one day and T20 24 31 . Two separate studies reported injuries in one day cricket only 36 47 .The use of a helmet at the time of sustaining a HNF injury was only reported in three studies 11 29 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded during the cumulative calculation as results were reported as per injury incidence rates 5 7 23 . A majority of studies (24/29) were undertaken in four cricket playing nations, namely South Africa 4 24 25 26 27 28 29 30 31 , Australia 5 7 23 32 33 34 , United Kingdom 11 35 36 37 38 and New Zealand 39 40 41 42 . As little as 11 of the included studies reported definitive age parameters, with eight of those studies reporting on cricketers aged 19 years or younger.…”
Section: Resultsmentioning
confidence: 99%
“…At present, there are few research studies that have been conducted in junior cricket and these are limited to Australia [18,19] and South Africa [20,21]. Together these studies have highlighted some important directions towards injury risks management and prevention in junior cricket.…”
Section: Injury Prevention In Cricket An Overview Of Injuries In Cricmentioning
confidence: 99%
“…Together these studies have highlighted some important directions towards injury risks management and prevention in junior cricket. In South Africa, Stretch and colleagues have conducted several epidemiological studies among schoolboy cricketers [20][21][22]. The other main contribution comes from Australia with the junior cricket project 'Juniors Enjoying Cricket Safely (JECS)' [18, [23][24][25].…”
Section: Injury Prevention In Cricket An Overview Of Injuries In Cricmentioning
confidence: 99%
“…Furthermore, with the introduction of different match formats, players are subjected to longer seasons and increased workloads. this means that they need to remain physically fit for extended time periods, specifically to reduce injury risk [4][5][6].…”
Section: Introductionmentioning
confidence: 99%